2019
DOI: 10.5056/jnm17106
|View full text |Cite
|
Sign up to set email alerts
|

Success and Complication Rates After Sacral Neuromodulation for Fecal Incontinence and Constipation: A Single-center Follow-up Study

Abstract: Background/AimsThe aim of this study was to evaluate the sustainability of sacral neuromodulation (SNM) success in patients with fecal incontinence (FI) and/or constipation.MethodsThis is a retrospective analysis of a prospective database of patients who received SNM therapy for FI and/or constipation between 2006 and 2015. Success rates, complications and reintervention rates were assessed after up to 10 years of follow-up.ResultsElectrodes for test stimulation were implanted in 101 patients, of whom 79 (78.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 45 publications
2
30
0
1
Order By: Relevance
“…A second issue relates to the requirement for battery (IPG) changes. The battery life of rechargeable devices has been estimated as 15 years compared to the longevity of the current InterStim II (IPG), which in clinical practice is about 5-7 years [11][12][13]. As a result of the claimed longer battery life of a rechargeable IPG, it has therefore been suggested that this therapy is associated with a reduced need for reoperation [14].…”
Section: Device Longevitymentioning
confidence: 99%
“…A second issue relates to the requirement for battery (IPG) changes. The battery life of rechargeable devices has been estimated as 15 years compared to the longevity of the current InterStim II (IPG), which in clinical practice is about 5-7 years [11][12][13]. As a result of the claimed longer battery life of a rechargeable IPG, it has therefore been suggested that this therapy is associated with a reduced need for reoperation [14].…”
Section: Device Longevitymentioning
confidence: 99%
“…The treatment of CPP and the therapy of incontinence after EM extraction is difficult and to this day still insufficient. S3 stimulation for incontinence by percutaneous or subcutaneous implantation techniques are based on blind implantation of the electrode (22,23). A great improvement in the treatment of pelvic pain was the LION technique introduced by Possover et al who first reported about the surgical and neuromodulative treatment options of sacral nerve stimulation after laparoscopic treatment of EM (2,19).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies and even a metanalysis exist on SNS for chronic constipation. While initial reports, on the wings of the enthusiasm around SNS, show a high success rate (over 70%) [5], almost all the subsequent studies have reported disappointing results after medium-/long-term evaluation, with a success rate around 30% [6][7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…SNS also improves other pelvic floor dysfunctions such as urinary retention [3], and constipation [4]. In particular, studies suggest improvement in constipation symptoms after SNS in both slow-transit and obstructed defecation, with success rates which vary from 22 to 73% depending on the length of the follow-up, irrespectively of the type of constipation [4][5][6][7][8][9][10][11]. However, the mechanisms of action of SNS have not yet been entirely elucidated.…”
Section: Introductionmentioning
confidence: 99%